I am Malala : The girl who stood up for education and was shot by the Taliban - Malala Yousafzai (Weidenfeld & Nicolson, 2013)
I come from a country which was created at midnight. When I almost died it was just after midday. When the Taliban took control of the Swat Valley, one girl spoke out. Malala Yousafzai refused to be silenced and fought for her right to an education. On Tuesday 9 October 2012, she almost paid the ultimate price. Shot in the head at point blank range while riding the bus home from school, few expected her to survive. Instead, Malala\'s miraculous recovery has taken her on an extraordinary journey from a remote valley in Northern Pakistan to the halls of the United Nations in New York. At sixteen, she has become a global symbol of peaceful protest and the youngest ever nominee for the Nobel Peace Prize. I Am Malala is the remarkable tale of a family uprooted by global terrorism, of the fight for girls\' education, and of Malala\'s parents\' fierce love for their daughter in a society that prizes sons. It will make you believe in the power of one person\'s voice to inspire change in the world.